Legal Protection Of Patients Regarding Healthcare Services at Unaccredited Private Dental Practices - Agus Gede Sutamaya; Nandang Sambas; Agus Hadian Rahim; A. Harits Nu’man; Dini Dewi Heniarti; Ida Bagus Nyoman Dhedy Widyabawa (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Accreditation of independent dental practices has become an important issue in dental health to ensure standards of quality and patient safety. Quality services, according to WHO dimensions (2018), require efforts for improvement both internally and externally, including accreditation every five years. The high incidence of patient safety events in various countries highlights the need for better protection. Accreditation is also implemented in other countries, such as Australia and Singapore, with significant support from local governments. Methods: This study employs a descriptive legal analysis method to outline criminal responsibilities. Data were collected through documentation of laws and relevant regulations. The analysis used a qualitative approach, linking the data to applicable legal provisions. Conclusions were drawn deductively to achieve a comprehensive understanding of the issues. Discussion: Patient safety has increasingly become a primary focus in managing healthcare facilities, especially due to the growing global attention to this issue. Data indicate that independent dental practices (TPMDG) can be high-risk facilities impacting patient safety. WHO (2009) identified four factors contributing to patient safety incidents: organizational, teamwork, environmental, and individual factors. Among these, organizational and teamwork factors significantly contribute to patient safety issues, including safety culture, leadership, and communication. Conclusion: Accreditation of independent dental practice locations is crucial to ensure the quality and safety of healthcare services through the implementation of strict standards and external oversight. Legal protection for patients receiving services at non-accredited practices can be achieved through several means in accordance with the applicable legislation in Indonesia.